COVID-19 vaccine hesitancy among university students: how worrying is it? An Italian survey. (20th October 2021) - Baccolini, V; Migliara, G; Renzi, E; Isonne, C; Massimi, A; De Vito, C; Marzuillo, C; Villari, P
Abstract: Background: With the availability of COVID-19 vaccines, vaccine hesitancy (VH) poses a great challenge to achieving herd immunity. Since young adults are usually asymptomatic, they may be less inclined to follow social distancing and mask-wearing guidelines. This study aimed at (i) quantifying VH among university students and (ii) investigating its determinants to identify barriers and predisposing factors to COVID-19 vaccination. Methods: Students physically attending Sapienza University of Rome during April 2021 were invited to take part in an online survey. The questionnaire explored sociodemographic variables, COVID-19 experience, attitude towards preventive measures, and COVID-19 vaccination. Hesitancy was measured as the complement to 10 of students' intention to get vaccinated and was modeled through zero-inflated negative binomial regression analysis. Results: Overall, 1949 students were surveyed. Most were females (59.9%) and aged 23.8±4.9 years on average. A great proportion reported no (76.8%) or slight hesitancy (15.7%). At multivariable analysis, in the count part, being more scared for the pandemic (IRR=0.94, 95%CI: 0.89-0.98), rating COVID-19 as more severe (IRR=0.93, 95%CI: 0.89-0.98) and being Italian rather than non-Italian (IRR=0.68, 95%CI: 0.54-0.85) were associated with lower VH, but no influence was found for age, sex, self-perceived risk of infection, and being a medical student. In the logit part, rating the vaccines as safe (b: 0.92, 95%CI: 0.75-1.10) or effective (b: 0.30, 95%CI: 0.14-0.45) decreased the likelihood of being hesitant. Conclusions: A few factors seemed to influence the intention to get vaccinated against COVID-19, including vaccine safety and effectiveness. Hence, attention should be given to planning effective communication about the vaccine profile in order to maintain and improve the public's confidence. Also, partnerships should be established among the stakeholders to ensure coordinated information sharing and dissemination. Key messages: Almost one-quarter of the surveyed students reported VH to some extent, and a few factors seemed to play a role in the vaccination decision-making process. Among others, the perceived vaccine safety and effectiveness seemed to influence VH. Attention should be given to planning effective communication about the vaccines' profile.